Poverty as an Obstacle for Travel: Domestic Tourism Activities in Spain - Altintas, Volkan; Tuzunkan, Demet (International Journal of Economics and Financial Issues, 2017)
In basic terms, income inequality, one of the economic inequalities that branch from social inequality, is used to define the income gap among individuals. Though a section of the population may benefit from overly high income, a larger section may continue to struggle with survival on very limited income. Income inequality impacts individual consumption and changes touristic product preferences, which have a high level of the elasticity of substitution. The numbers for income inequality based on the Gini coefficient have been attained from OECD data, and the changes in domestic tourism activities in years with ascending or descending income inequality have been attained from UNWTO data and interpreted within this framework. Spain has been chosen for a sample study for the attention it draws as a European Union country with high income inequality and high domestic tourism potential. Keywords: Tourism, Spain, Poverty, Gini Coefficient, Inequality JEL Classifications: D63, I32, L83, Z3